Leaf Waxes and Hemicelluloses in Topsoils Reflect the δ2H and δ18O Isotopic Composition of Precipitation in Mongolia - Struck, Julian; Bliedtner, Marcel; Strobel, Paul; Bittner, Lucas; Bazarradnaa, Enkhtuya; Andreeva, Darima; Zech, Wolfgang; Glaser, Bruno; Zech, Michael; Zech, Roland (Frontiers in Earth Science, 2020)
Compound-specific hydrogen and oxygen isotope analyzes on leaf wax-derived n-alkanes (δ2Hn alkane) and the hemicellulose-derived sugar arabinose (δ18Oara) are valuable, innovative tools for paleohydrological reconstructions. Previous calibration studies have revealed that δ2Hn alkane and δ18Oara reflect the isotopic composition of precipitation, but – depending on the region – may be strongly modulated by evapotranspirative enrichment. Since no calibration studies exist for semi-arid and arid Mongolia so far, we have analyzed δ2Hn alkane and δ18Oara in topsoils collected along a transect through Mongolia, and we compared these values with the isotopic composition of precipitation (δ2Hp-WM and δ18Op-WM, modelled data) and various climate parameters. δ2Hn alkane and δ18Oara are more positive in the arid south-eastern part of our transect, which reflects the fact that also the precipitation is more enriched in 2H and 18O along this part of the transect. The apparent fractionation Ɛapp, i.e. the isotopic difference between precipitation and the investigated compounds, shows no strong correlation with climate along the transect (Ɛ2H n C29/p = -129 ± 14‰ , Ɛ2H n C31/p = -146 ± 14‰, and Ɛ18O ara/p = +41 ± 2‰). Our results suggest that δ2Hn alkane and δ18Oara in topsoils from Mongolia reflect the isotopic composition of precipitation and are not strongly modulated by climate. Correlation with the isotopic composition of precipitation has root-mean-square errors of 13.4‰ for δ2Hn-C29, 12.6 for δ2Hn-C31, and 1.2‰ for δ18Oara, so our findings corroborate the great potential of compound-specific δ2Hn alkane and δ18Oara analyzes for paleohydrological research in Mongolia.